Open Access: When knowledge unifies nations... - PANAYIOTOPOULOS (Δ. ΠΑΝΑΓΙΩΤΟΠΟΥΛΟΣ) D. (Journal of the Hellenic Veterinary Medical Society, 2017)
The World Wide Web disseminates scientific knowledge. The possibility of searching and retrieving simultaneously scientific publications tends to promote research and ensures originality. The traditional publishing model restricted research to published subscription-based journals, thus providing scientific information only to financially sound communities. In response to this, the Open Access movement was created, which is an economical way of diffusion and management of scientific information. As a result, scientific information is now available to all for free spreading research activity worldwide, while encouraging communication and interoperability in areas of diverse research interests. This article discusses the phenomenon of open access. Also, open access journals and repositories are referred as well as modern ways of disseminating research to the public.